2006
DOI: 10.1007/s11187-006-0014-y
|View full text |Cite
|
Sign up to set email alerts
|

Invariances and Diversities in the Patterns of Industrial Evolution: Some Evidence from Italian Manufacturing Industries

Abstract: This work explores and compares some basic properties of corporate growth process at both aggregate manufacturing level and disaggregated sectoral levels. Using an extensive dataset on Italian manufacturing firms, we investigate which properties of firm growth dynamics are robust under disaggregation. We compare the results obtained with three different definitions of firm size, namely total sales, number of employees and value added. Our analysis suggests that while different sectors are characterized by sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
86
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 30 publications
11
86
0
2
Order By: Relevance
“…The issue of the dependence of growth on size is an old one within the traditional Gibrat's law framework. On this point, previous analysis based on a similar sample of Italian manufacturing (see Bottazzi et al (2007)) has not found any dependence between sales levels and sales growth. In addition, recent studies show that the time scale of growth processes can vary between small and large firms: whilst small firms display significant negative autocorrelation in annual growth rates (measured in terms of sales and employment), larger firms experience positive autocorrelation, which is consistent with the idea that they plan their growth projects over a longer time horizon (Coad, 2007a).…”
Section: Size Disaggregationmentioning
confidence: 65%
See 2 more Smart Citations
“…The issue of the dependence of growth on size is an old one within the traditional Gibrat's law framework. On this point, previous analysis based on a similar sample of Italian manufacturing (see Bottazzi et al (2007)) has not found any dependence between sales levels and sales growth. In addition, recent studies show that the time scale of growth processes can vary between small and large firms: whilst small firms display significant negative autocorrelation in annual growth rates (measured in terms of sales and employment), larger firms experience positive autocorrelation, which is consistent with the idea that they plan their growth projects over a longer time horizon (Coad, 2007a).…”
Section: Size Disaggregationmentioning
confidence: 65%
“…11 Table 1 shows year-wise summary statistics, which provide the reader with an idea of 6 The database has been made available under the mandatory condition of censorship of any individual information. (Bottazzi et al, 2007), showing that the growth rate distributions of Italian firms are well approximated by a Laplace (or symmetric exponential) distribution. Finally, we also notice that the distribution of growth rates of GOS has a particularly wide support, which would indicate considerable heterogeneity between firms in terms of the dynamics of their profits.…”
Section: Data and Variablesmentioning
confidence: 97%
See 1 more Smart Citation
“…Chesher, 1979;Bottazzi et al, 2001) while others report a negative serial correlation (e.g. Boeri and Cramer, 1992;Bottazzi et al, 2007). Even further studies have failed to find any autocorrelation in the data (e.g.…”
Section: Notesmentioning
confidence: 97%
“…Whether there exists a large literature on size and productivity differences among firms (a comprehensive survey is that in Bartelsman and Doms, 2000, for Italy refer to Bottazzi et al, 2007Bottazzi et al, , 2005 there is much less evidence documenting differences in the cost of labor of firms. In this respect, we begin by showing the degree of heterogeneity in the cost of labor for firms belonging to the same three-digit sector.…”
mentioning
confidence: 99%